1998
DOI: 10.1046/j.1365-2044.1998.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose intra‐articular ketorolac for pain relief following arthroscopy of the knee joint

Abstract: SummaryIn a double-blind, placebo-controlled study of 90 ASA 1 and 2 patients scheduled for elective surgery we compared the effect of pre-administering midazolam 2 mg or propofol 30 mg on the dose of propofol subsequently required to induce anaesthesia. Using loss of response to verbal command and tolerance to placement of a facemask as end-points, the dose of propofol required to induce anaesthesia was significantly smaller in the patients given propofol (1.87 mg.kg À1 ) or midazolam (1.71 mg.kg À1) when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Since the pain after arthroscopic surgery may be due to the site of reconstruction, patellar tendon graft and inflammation, oedema and the hyperalgesic substances produced [5,13,20], antiinflammatory agents, such as nonsteroidal drugs (NSAIDs) and steroids, either applied systemically or locally, may help to reduce inflammation and swelling, which may occur, and reduce pain and consequent analgesic consumption. Wang et al [20] reported a study on postoperative efficacy of intraarticular triamcinolone application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pain after arthroscopic surgery may be due to the site of reconstruction, patellar tendon graft and inflammation, oedema and the hyperalgesic substances produced [5,13,20], antiinflammatory agents, such as nonsteroidal drugs (NSAIDs) and steroids, either applied systemically or locally, may help to reduce inflammation and swelling, which may occur, and reduce pain and consequent analgesic consumption. Wang et al [20] reported a study on postoperative efficacy of intraarticular triamcinolone application.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been done to prolong analgesia such as supplementing with ketamine, clonidine, morphine or nonsteroidal analgesics [5,8,17]. Nonsteroidal analgesics are found to be effective in improving analgesia after arthroscopic knee surgery, but the optimal route is still speculative [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Intra-articular ketorolac injection reduces joint inflammation and postoperative pain in the knee in both clinical and animal models. 30,36,37 Although the local anti-inflammatory action of ketorolac in the periphery may contribute to its analgesic effects, other studies report that ketorolac reduces excitatory peptides in the dorsal horn after partial sciatic nerve ligation, which has been correlated with a reduction in pain. 38 Our laboratory has shown that a single joint injection of ketorolac given after a painful facet joint injury can attenuate pain only when it is given after pain has developed, although the specific mechanism of action was not determined.…”
Section: Introductionmentioning
confidence: 99%
“…They further report on the synergistic effect of this combination (10). In another study involving 60 patients by Convery et al, a local injection of ketorolac was found to as equally effective as 10 mg systemic dose with regard to analgesia or postoperative visual analogue pain scores 2 . In addition, De Andres et al have reported higher success ratio in the group which received intramuscular ketorolac along with i.a.…”
Section: Administration Cook Et Al Have Emphasized Thementioning
confidence: 92%
“…Ketorolac is a strong nonsteroidal anti-inflammatory agent, has been considered a powerful alternative to other NSAIDs and opioids in postoperative pain treatment and following knee arthroscopic surgery. It is also promising for the treatments of renal colic, acute muscle and bone pains, and ocular inflammation (2,5,7).…”
Section: Introductionmentioning
confidence: 99%